Purchase intention of counterfeit fashion products among young generation / Azira Farhana Aidi Zamri - Aidi Zamri, Azira Farhana (Faculty of Business and Management, 2019)
The purpose of this study is to examine the determinants of purchase intention of counterfeit fashion products among young generation. It helps companies to understand the main factors that influence purchase intention of counterfeit fashion products. The questionnaires survey via an online survey was used for online data collection by 200 respondents among the young generation in the Shah Alam City. Convenient sampling was employed and Statistical Package for Social Science (SPSS) version 20 was used to analyse the data. Pearson correlation, and multiple regressions were used to test the research hypotheses. It is found that past experience found significant in influencing the young generation’s purchase intention towards counterfeit fashion products. Additionally, the product knowledge and social influence have positively affects the purchase intention towards counterfeit fashion products. Meanwhile, perceived risk has a negative effect on purchase intention towards counterfeit fashion products. The other variables for this research study should be included and investigated in the future. It is expected that the study findings will enhance the understanding of marketers as well as policymakers about consumers’ purchase intention of such fake products. Eventually, it will help them to come up with better marketing strategies to purchase counterfeit products and to encourage them to purchase the original product.